Labyrinth moments: Evidencing reflexivity in intersectional research using constructivist grounded theory - Forbay, T. R.; Mnguni, P. P. (South African Journal of Higher Education, 2024)
Qualitative research is, oftentimes, an emotional, relational, political and intellectual rollercoaster ride. This heightens the risk of methodological, ethical and relational fallouts. Constructivist grounded theory enables researchers to confront the multiple ways in which deeply embedded aspects of identity, personal values, biases and emergent research relationships impact the research process. In this article, we demonstrate how a reflexive stance in constructivist grounded theory enhances bracketing and loosens the grip of both positionality and methodolatry. The discussion draws on the lived experiences of conducting and supervising autobiographically inclined doctoral research. The article underscores the need for a strong reflexive stance, not just during fieldwork, but right from the onset, at the conceptualisation stage. A reflexive stance, on the part of both students and supervisors stands to benefit the decolonisation project and can help guard against epistemic violence.